Factors Contributing to the Fluctuation in Residential Construction in Iran - Fereidouni, Hassan Gholipour (UTS ePRESS, 2011)
Residential construction is one of the most important pillars of Iran‟s economy. Although this sector had an increasing trend over the past two decades, the growth rate of residential construction has been very volatile. The purpose of this paper is to empirically investigate those factors contributing to this fluctuation over the 1991:Q2-2008:Q4. By applying cointegration approach, the empirical results show that housing prices, construction costs, GDP and gold prices are important factors to predict changes in the level of residential construction in Iran.